Toxicological and Immunological Effects oÂ·f th.e Insecticide Diazinon in Male Albino Mice
This st4dy has been ccil’ndÂ·uctedÂ· to Â·shed a1ight 00: the tox:icologital Â®d irmm.J,nological effects.of the insectiCide Diaziuon on male albino mice. In order to determine the dose whiCh should be utin he chrqn:ic exposure study, the LD:so valubas established which rea.ched 58 mg l kg of b0dy weight . Various parameters wereÂ· utHizea in • evaluatitig’the effects of tb:e.Â·ins.ecticide in fo.ut Weeks ami ig